Effects of intensive human management on the taxonomic and functional diversity of ground beetles in a planted forest landscape - Nanni, Analía Soledad (2021)
The rapid expansion of planted forests harms native biodiversity. Few studies report the effects of replacing wetlands with planted forests on ground beetles. We analyze how the taxonomic and functional diversity of ground beetles are affected by intensive management of a planted forest landscape in the Lower Delta of the Parana River. We defined six habitat types (n = 3, N = 18): young and mature willow (YW, MW), young and mature poplar without cattle (YP, MP), young and mature silvopastoral poplar (YS, MS). Using pitfall traps (N = 1728), we recorded 35 species (1896 individuals). YW and MS reached the highest taxonomic diversity and richness. YW with more vertical heterogeneity showed higher species richness than MW. Hydrophilic species were more abundant in YW. Zoophagous species were more abundant in MS. YS, MS, and YW reached the highest functional evenness, which implies that a large part of the functional niches was used. Cattle dung and freshwater canals for livestock offer more resources for ground beetles. The planted tree species, stand age, and presence of cattle affects taxonomic and functional diversity of ground beetles. Willow and silvopastoral planted forests are the most suitable habitats for hosting wetland species. So, we recommend using willow species rather than poplar species when planted forests replace fluvial wetlands, increasing irrigation of poplar planted forests through ditches and canals, conserving or restoring different strata of understory to increase vertical heterogeneity, and maintaining the landscape heterogeneity. These management measures are essential to prevent the loss of wetland species and conserve ground beetle’s diversity.